Central airway collapse is related to obesity independent of asthma phenotype. Issue 4 (5th January 2021) - Bhatawadekar, Swati A.; Peters, Ubong; Walsh, Ryan R.; Daphtary, Nirav; MacLean, Erick S.; Mori, Vitor; Hodgdon, Kevin; Kinsey, C. Matthew; Kaminsky, David A.; Bates, Jason H.T.; Dixon, Anne E.
ABSTRACT: Background and objective: Late‐onset non‐allergic asthma in obesity is characterized by an abnormally compliant, collapsible lung periphery; it is not known whether this abnormality exists in proximal airways. We sought to compare collapsibility of central airways between lean and obese individuals with and without asthma. Methods: A cross‐sectional study comparing luminal area and shape (circularity) of the trachea, left mainstem bronchus, right bronchus intermedius and right inferior lobar bronchus at RV and TLC by CT was conducted. Results: In 11 lean controls (BMI: 22.4 (21.5, 23.8) kg/m 2 ), 10 lean individuals with asthma (23.6 (22.0, 24.8) kg/m 2 ), 10 obese controls (45.5 (40.3, 48.5) kg/m 2 ) and 21 obese individuals with asthma (39.2 (35.8, 42.9) kg/m 2 ), lumen area and circularity increased significantly with an increase in lung volume from RV to TLC for all four airways ( P < 0.05 for all). Changes in area and circularity with lung volume were similar in obese individuals with and without asthma, and both obese groups had severe airway collapse at RV. In multivariate analysis, change in lumen area was related to BMI and change in circularity to waist circumference, but neither was related to asthma diagnosis. Conclusion: Excessive collapse of the central airways is related to obesity, and occurs in both obese controls and obese asthma. Increased airway collapse could contribute to ventilation abnormalities in obese individuals particularly at lower lung volumes, and complicate asthma in obese individuals. Abstract : We compared collapsibility of central airways in lean and obese individuals with and without asthma by CT from changes in airway luminal area and circularity at reduced lung volume. Our results indicate that obesity is characterized by excessive central airway collapse. See related Editorial